Design and research of a three-dimensional negative Poisson's ratio structure - Shen, Jiarong; Wu, Maoliang; Wang, Qisheng; Qi, Ping (SPIE, 2023)
After more than 20 years of development, metamaterials have gradually become an important subject in new material technology since their birth in the early century. As an important part of modern metamaterials, materials with negative Poisson's ratio have been applied in aerospace, military industry, medical and health care, satellite, automobile, ship, transportation and packaging and other fields [1-5]. In this paper, a three-dimensional negative Poisson's ratio structure is designed, and the influence of its structural parameters on mechanical properties is studied through theoretical calculation and simulation. The negative Poisson's ratio performance of three-dimensional negative Poisson's ratio structure in multiple directions makes it promising to be applied in a variety of occasions.